1982
DOI: 10.1093/bja/54.10.1117
|View full text |Cite
|
Sign up to set email alerts
|

Dural Permeability to Narcotics: In Vitro Determination and Application to Extradural Administration

Abstract: The permeability of cranial and lumbar dura to various substances including a number of narcotic analgesics was measured in vitro. Preliminary data On human postmortem material is reported. Permeability had a linear relation to the inverse of the square root of molecular weight. This is the expected relationship for a diffusion process dependent upon molecular weight. The differential mass selectivity coefficients for lumbar and cranial dura were calculated; they were similar at 0.8 and 0.9. This was greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(36 citation statements)
references
References 22 publications
1
34
0
1
Order By: Relevance
“…Compared with morphine, which tends to linger in the water phase in the cerebrospinal fluid (CSF) and spread more widely and rostrally 26 in the spinal canal due to its hydrophylicity, buprenorphine can reach the brain more quickly due to the rapid uptake into :the epidural veins, as Moore et al suggested. 27 The high lipophilicity and relatively small molecular weight of buprenorphine lead to rapid vascular removal. Late respiratory depression was not recorded in the 48 hr after surgery in any group, probably because epidural administration of morphine 80 lag.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with morphine, which tends to linger in the water phase in the cerebrospinal fluid (CSF) and spread more widely and rostrally 26 in the spinal canal due to its hydrophylicity, buprenorphine can reach the brain more quickly due to the rapid uptake into :the epidural veins, as Moore et al suggested. 27 The high lipophilicity and relatively small molecular weight of buprenorphine lead to rapid vascular removal. Late respiratory depression was not recorded in the 48 hr after surgery in any group, probably because epidural administration of morphine 80 lag.…”
Section: Discussionmentioning
confidence: 99%
“…The time from the epidural administration of the agents until the first request for pentazocine for postoperative pain relief was 10.0 _+ 5.1 hr (mean _+ SE) in Group I , 37.7 _+ 4.7 hr in Group II, 27.1 _+ 7.1 hr in Group III, and 44.4 :t: 4.1 hr in Group IV. The duration of analgesia in Groups II, HI and IV was longer than that of Group I (P < 0.05).…”
Section: Duration Of Analgesiamentioning
confidence: 98%
“…Penetration of the dura is considerably influenced by lipophilicity, but molecular weight may also play an important role. 19 Following epidural administration, cerebrospinal fluid concentrations of fentanyl peak in 10 to 20 rain 2~ while sufentanil concentrations peak in about six minutes. 21 In contrast, cerebrospinal fluid concentrations of morphine, following epidural administration, peak in one to four hours.…”
Section: Phmnacokinefics Of Intmthecal and Epidural Opioidsmentioning
confidence: 99%
“…Todavia, apesar de o tempo anestésico não ter sido prolongado pela clonidina, a maior dispersão cranial do bloqueio foi confirmada neste estudo, de modo que, em 50% dos animais, o bloqueio atingiu até a primeira vértebra lombar, enquanto o uso isolado da lidocaína permitiu bloqueio máximo até a quarta vértebra lombar, resultados que concordam com relatos anteriores (GASPARINI et al, 2007;CASSU et al, 2010). A propagação cranial do bloqueio anestésico pode ser obtida mediante a administração de volumes elevados no espaço peridural, bem como em função das propriedades físico químicas dos fármacos empregados (MOORE et al, 1982). No atual estudo, o volume administrado no espaço peridural foi o mesmo em ambos os tratamentos, visto que, no tratamento C, o volume de lidocaína foi reduzido, visando-se a perfazer o volume final de 0,25ml kg -1 , conforme preconizado pela literatura (GASPARINI et al, 2007;CASSU et al, 2010).…”
Section: Discussionunclassified